Synthesis Of 2-substituted N-heterocycles via asymmetric organocatalysed intramolecular N-conjugate addition - Grant, Kevan Michael (2017)
This thesis describes the use of cinchona derived squaramide catalyst 27 in the asymmetric intramolecular N-conjugate addition of nitrogen nucleophiles with a,B-unsaturated carbonyls. The first chapter describes investigation of intramolecular N-conjugate addition reactions of sulfonamides with aromatic ketones, esters, thioesters and amides generating chiral 2-substituted piperidines, morpholines and oxazinanes. The squaramide catalyst 27 was found to efficiently catalyse the reaction, good yields of cyclic products were obtained with excellent enantioselectivities. Further modification of these products towards natural and drug targets is outlined. A possible mechanism based on observed stereochemistry and in silico modelling of transition states is proposed. The second chapter describes investigation of altered substrates formed by varying functionality linking the a,B-unsaturated carbonyl to the nitrogen nucleophile. For example, 4-Substitued 3,4-dihydro-2H-benzo[e][1,3]oxazin-2-ones and cyclic sulfamates were synthesised this way, but unfortunately enantioselectivity was poor in this case. Finally the influence of chiral substrates on asymmetric cyclisation was investigated during the synthesis of 2,4-disubstituted pyrrolidines. It was found that the intrinsic diastereoselectivity of the cyclisation is difficult to overcome using asymmetric organocatalysis.